Viabilidad de espermatozoides de ovinos en diferentes sistemas de refrigeración - Moscardini, Murillo Mansano; Scott, Caroline; Moura, Diego Souza; Lourenço, Tarcísio Torre; Aristizábal, Viviane Helena Vallejo [UNESP]; Souza, Fabiana Ferreira de [UNESP] (Editora Cubo, 2014)
The aim of this study was to evaluate the ovine sperm quality colled in thermal boxs. Six ejaculates from 2 rams were collected using artificial vagina. Samples were analyzed to volume, mass movement, motility, vigor, sperm cell concentration, hypo-osmotic swelling test and supravital stain. Ejaculates were divided into 2 aliquots and diluted in 0.9% NaCl or in the extender (Botubov®, Botupharma, Botucatu, SP, Brazil), and was kept at room temperature, refrigerator (5°C), Botubox® (15°C, Botupharma, Botucatu, SP, Brazil), Botutainer® (5ºC, Botupharma, Botucatu, SP, Brazil) and MaxSemen® (15°C, EHG Agrofarma, Campinas, SP, Brazil). All samples were analyzed each 24 hours to the same parameters. According to the results the samples diluted and cooled in extender preserved sperm viability until 48 hours in thermal boxes and in refrigerator; and the samples extended preserved in environment maintained motility 30% up to 72 hours. Samples diluted in 0.9% saline retained motility around 30% until 24 hours of cooling. Based on the results it is concluded that the three boxes may be used for transport of ram semen, diluted and refrigerated for a period of 24 to 48 hours.

El objetivo del presente estudio fue evaluar la cualidad espermática del semen refrigerado de carneros, en cajas térmicas con diferentes temperaturas. Fueron utilizados 6 eyaculados, de 2 carneros colectado con vagina artificial. En el semen se analizó volumen, movimiento en masa, motilidad, vigor, concentración espermática, test hipo-osmótico y coloración supra-vital. Las muestras fueron divididas en 2 alícuotas y diluidas en solución NaCl 0,9% o en un medio (Botubov®, Botupharma, Botucatu, SP, Brasil); después, la dilución fue mantenida a temperatura ambiente, nevera (5ºC), caja Botubox® (15ºC, Botupharma, Botucatu, SP, Brasil), caja Botutainer® (5ºC, Botupharma, Botucatu, SP, Brasil) y caja MaxSemen® (15ºC, EHG Agrofarma, Campinas, SP, Brasil). Todas las muestras fueron analizadas cada 24 horas, siguiendo los mismos parámetros. De acuerdo con los resultados, las muestras mantenidas en el diluyente presentaron viabilidad hasta 48 horas de refrigeración en las cajas térmicas y en la nevera, y la motilidad se mantuvo entorno de 30% hasta las 72 horas. Las muestras diluidas en solución NaCl 0,9% conservaron la motilidad en 30% hasta las 24 horas de refrigeración. Basado en los resultados se concluye que las tres cajas pueden ser utilizadas para transporte de semen ovino, diluido y refrigerado por un período de 24 a 48 horas.
Viability of ram sperm chilled at 5º and 15ºC in different cooling systems
Keywords: Cryopreservation; Ram; Spermatozoa; Carnero; Crio-preservación; Espermatozoide